RETRACTED: Problems of reconstruction of Shchelkovskoe highway in the Moscow region - Mezentsev Sergei; Krasheninnikova Evgenija; Norenkov Sergei; Gavrikov Denis (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001